2012
DOI: 10.1038/gt.2012.71
|View full text |Cite
|
Sign up to set email alerts
|

Viral dose, radioiodide uptake, and delayed efflux in adenovirus-mediated NIS radiovirotherapy correlates with treatment efficacy

Abstract: We have constructed a prostate tumor specific conditionally replicating adenovirus (CRAd), named Ad5PB_RSV-NIS that expresses the human sodium iodine symporter gene (hNIS). LNCaP tumors were established in nude mice and infected with this CRAd to study tumor viral spread, NIS expression, and efficacy. Using quantitative polymerase chain reaction (QPCR) we found a linear correlation between the viral dose and viral genome copy numbers recovered after tumor infection. Confocal microscopy showed a linear correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…4 Cloning of NIS in 1996, 5,6 as one of the major milestones in thyroidology in the last 20 years, opened the way for the use of this potent dual reporter and therapy gene concept in the treatment of a broad range of cancer types by targeting NIS to nonthyroidal cancer cells. Extensive characterization of the applicability of NIS as a diagnostic and therapeutic gene by several research groups, including our own, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] revealed NIS to be a remarkable and powerful tool for detecting and treating different extrathyroidal cancer types, even in metastatic disease. [25][26][27][28] The high incidence of hepatocellular carcinoma (HCC) as a result of a late diagnosis and a poor prognosis along with limited treatment strategies urgently requires the development of new treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…4 Cloning of NIS in 1996, 5,6 as one of the major milestones in thyroidology in the last 20 years, opened the way for the use of this potent dual reporter and therapy gene concept in the treatment of a broad range of cancer types by targeting NIS to nonthyroidal cancer cells. Extensive characterization of the applicability of NIS as a diagnostic and therapeutic gene by several research groups, including our own, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] revealed NIS to be a remarkable and powerful tool for detecting and treating different extrathyroidal cancer types, even in metastatic disease. [25][26][27][28] The high incidence of hepatocellular carcinoma (HCC) as a result of a late diagnosis and a poor prognosis along with limited treatment strategies urgently requires the development of new treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…A NIS gene delivered with an adenovirus vector and a tissue-specific gene promoter, the prostate-specific antigen gene (PSA) promoter, conferred efficient functional NIS expression in prostate cancer xenografts [ 79 , 80 ]. In a recent report, Trujillo and coworkers, by using a prostate tumor–specific CRAd in a xenograft model of prostate cancer, demonstrated that the efficacy of radioiodide therapy depends mainly on an efficient viral tumor spread and a decrease in the rate of the efflux of radioisotope [ 81 ]. To achieve synergistic or additive cytotoxic effects, combined treatments with NIS gene therapy and a tumor targeting strategy, such as utilization of an oncolytic vector [ 82 ], are also under experimentation.…”
Section: Introductionmentioning
confidence: 99%
“…Although SSTR2 was not employed previously for CRAd monitoring, several groups reported the use of human NIS as a reporter gene for imaging of various CRAd agents following intratumoral injection in animal models of colorectal, 63,65 prostate, 60,66,67,[94][95][96] and peritoneal ovarian cancer. 62 These SPECT imaging studies show that human NIS expression reaches a peak 2 to 4 days after intratumoral injection, followed by a sharp disappearance of human NISdependent accumulation of radiotracer.…”
Section: Discussionmentioning
confidence: 99%